2018
DOI: 10.1111/ddi.12754
|View full text |Cite
|
Sign up to set email alerts
|

Land use legacy effects on woody vegetation in agricultural landscapes of south-western Ethiopia

Abstract: Aim: Past land use legacy effects-extinction debts and immigration credits-might be particularly pronounced in regions characterized by complex and dynamic landscape change. The aim of this study was to evaluate how current woody plant species distribution, composition and richness related to historical and present land uses.Location: A smallholder farming landscape in south-western Ethiopia. Methods:We surveyed woody plants in 72 randomly selected 1-ha sites in farmland and grouped them into forest specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…However, the differences between agroforests of contrasting land‐use history might diminish over time. Oftentimes, forest‐derived agroforests lose tree cover due to logging of existing trees, natural mortality and limited recruitment (De Beenhouwer et al., 2016; Shumi et al., 2018; Valencia et al., 2016), typically resulting in a reduction of biodiversity (Philpott et al., 2008; Tscharntke et al., 2011). Contrastingly, open‐land‐derived agroforests gain tree cover over time and could thereby enter into a positive biodiversity trajectory (Perfecto et al., 1996).…”
Section: Land‐use History Shapes Vegetation Structure and Biodiversitymentioning
confidence: 99%
“…However, the differences between agroforests of contrasting land‐use history might diminish over time. Oftentimes, forest‐derived agroforests lose tree cover due to logging of existing trees, natural mortality and limited recruitment (De Beenhouwer et al., 2016; Shumi et al., 2018; Valencia et al., 2016), typically resulting in a reduction of biodiversity (Philpott et al., 2008; Tscharntke et al., 2011). Contrastingly, open‐land‐derived agroforests gain tree cover over time and could thereby enter into a positive biodiversity trajectory (Perfecto et al., 1996).…”
Section: Land‐use History Shapes Vegetation Structure and Biodiversitymentioning
confidence: 99%
“…In line with this, the empirical findings by Jiren et al (2017) in our study area showed that many local people favoured multifunctionality-oriented land management. Such integrated land management may be rooted in historical land use, as indicated by a higher woody plant species richness in long-established compared to more recently converted farmland (Shumi et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the region, while the landscape harbours a high diversity of woody plant species that provide key services for local people (e.g. Jara et al 2017;Shumi et al 2018Shumi et al , 2019b, current agricultural policies favour agricultural intensification (e.g. Kassa et al 2016) and thus negatively impact woody plant species diversity and associated ES.…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted in subsistence-dominated rural landscapes of six kebeles (the lowest administrative unit) located in the Gera, Gumay and Setema districts of Jimma Zone, Oromia Regional State, southwest Ethiopia ( Figure 1). The kebeles were selected to span a gradient in forest cover, ranging from 11% to 84% within a kebele ( Figure 1(c,d)) (for specific details see Shumi et al 2018). The region is characterised by a mosaic of forest, farmland (arable land, grazing land and homegardens) and settlements.…”
Section: Study Areamentioning
confidence: 99%